2015
DOI: 10.1111/jori.12069
|View full text |Cite
|
Sign up to set email alerts
|

Market Expectations Following Catastrophes: An Examination of Insurance Broker Returns

Abstract: We investigate the effect major catastrophes are expected to have on equilibrium price and quantity in the insurance market. In particular, we examine whether investors expect total industry revenue to increase following a disaster's shock to insurers' financial capital. Rather than examine insurers directly, we study insurance brokers, who earn commissions on premium revenue but do not pay losses following a disaster. We conduct an event study on insurance broker stock returns surrounding the 43 largest insur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 43 publications
(54 reference statements)
0
17
0
Order By: Relevance
“…Kaplanski and Levy (2010) discuss the impact of aviation accidents on stock prices and believe that unstable stock prices are more vulnerable to this effect. Ragin and Halek (2016) studied the 43 largest disasters in the insurance industry since 1970 and found that insurance brokers received abnormal stock returns on the day of the incident. Al Rjoub (2009) analyzed the impact of the financial crisis on the stock market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kaplanski and Levy (2010) discuss the impact of aviation accidents on stock prices and believe that unstable stock prices are more vulnerable to this effect. Ragin and Halek (2016) studied the 43 largest disasters in the insurance industry since 1970 and found that insurance brokers received abnormal stock returns on the day of the incident. Al Rjoub (2009) analyzed the impact of the financial crisis on the stock market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although, in the present paper, a model is proposed with the flexibility of different interest rates, aggregate claims, payoff structures and the underlying distributions, the relationship between the nuclear power risks and the financial market risks is not considered in our framework. In the literature (Gürtler et al 2016;Ragin and Halek 2016) examined the impact of natural catastrophes and financial crises on the CAT risk bond premiums. It would be interesting though to consider the case of terrorism as a future extension of the current model (Allison 2005;Kunreuther et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…One of the very few empirical papers on this important topic uses the data on 1800 large U.S. corporations and concludes that the insurance industry gests a boom in premium income after catastrophic incidents (Michel-Kerjan et al, 2015). Another study using 43 large catastrophic-insured incidents since 1970, finds a significant increase in industry revenues and stock returns of insurance brokers, right after such incidents (Ragin & Halek, 2016). The COVID-19 has had a severe negative impact on the Chinese insurance industry and caused a reduction in all kinds of inflows, including both commercial and individual premiums.…”
Section: Introductionmentioning
confidence: 99%